PENGARUH PEMBERIAN EDUKASI TENTANG SADARI TERHADAP PELAKSANAAN SADARI PADA REMAJA PUTRI - Chiot, Okti Satria; Andriani, Yessi; Oviana, Athica (Jurnal Sains, Teknologi dan Kesehatan, 2023)
Based on data (WHO, 2016), says that the number of women, especially young women who suffer from breast cancer reaches 1,150,000, of which 700,000 live in developing countries, one of which is Indonesia. In 2019, the incidence of breast cancer in West Sumatra Province increased to 479 people. This study aims to determine the effect of providing education on BSE on the implementation of BSE in Young Women at SMAN 2 Tilatang Kamang. The research design used the Quasi Experiment method with the research design "One group pretest posttest design. This research was carried out on July 2 to 23 at SMAN 2 Tilatang Kamang, the number of research samples was 47 people, with a total sampling technique. The research instrument used a questionnaire observation sheet and the data were processed univariate and bivariate. In this study, the results obtained that the average implementation of BSE before being given education about BSE is 19.15, the average implementation of BSE after being given education about BSE is 28.85. The statistical test results obtained p value 0.000. The conclusion in this study is that there is an effect of providing education about BSE on the Implementation of BSE for Young Women at SMAN 2 Tilatang Kamang. Therefore, it is recommended that adolescents increase their knowledge about breast cancer prevention so that they can avoid breast cancer while reducing the incidence of cancer.